Effective Protection Against Status Epilepticus Caused by Lithium–Pilocarpine: Combination of Midazolam and Lacosamide - Cumaali Demirtas; Metehan Akca; Ugur Aykin; Yunus Emre Surmeneli; Hava Yildirim; Mehmet Yildirim (Brain and Behavior)
ABSTRACT Aim Status epilepticus causes the most severe condition related to epilepsy in terms of high mortality rate. Although status epilepticus treatment guidelines specify a treatment process based on three‐stage monotherapy, effective control cannot yet be achieved in all cases. In the presented study, with electrophysiological and behavioral tests, it was aimed to investigate the effectiveness of the combination of midazolam (MDZ), one of the most commonly used benzodiazepines in the first‐line treatment of status epilepticus, with the second‐line antiepileptics levetiracetam (LEV), lacosamide (LCM), valproic acid (VPA), and fosphenytoin (fPHT). Methods A status epilepticus model was created with lithium–pilocarpine (5 mEq/kg–320 mg/kg) in adult male Sprague–Dawley rats with implanted electroencephalography (EEG) electrodes. MDZ (9 mg/kg) alone or in dual combinations with antiepileptic drugs (200 mg/kg LEV, 50 mg/kg LCM, 300 mg/kg VPA, 100 mg/kg fPHT) was injected i.p. to the experiment groups with status epilepticus. After video‐EEG recordings were taken from the rats during and after status, the effects of drug interactions on cognitive and motor behaviors were examined by applying behavioral tests (open field, Rotarod, radial arm maze, and passive avoidance). Results Compared with the untreated status epilepticus group, it was determined that MDZ alone and the combination of four antiepileptic drugs administered with MDZ significantly reduced the mortality rate, spike frequency, and spike amplitude of epileptic seizures and suppressed epileptic seizures at certain levels (p < 0.01). Compared to MDZ monotherapy, it was determined that the mortality rate and spike frequency and amplitude decreased significantly in the MDZ + LCM group (p < 0.01), whereas on the other hand, mortality and spike frequency increased in the MDZ + LEV group (p < 0.01). No negative effects were observed in learning and memory in all treatment groups, but it was determined that the motor functions of the animals treated with MDZ + fPHT were impaired compared to both the control group without any treatment and the MDZ group (p < 0.01). Conclusion In the status epilepticus model induced by lithium–pilocarpine, the combination of MDZ + LCM was found to be the most effective polytherapy option in reducing seizures and mortality. Additionally, it was observed that LEV, LCM, and VPA administered together with MDZ did not negatively affect both cognitive and motor functions.